2019
DOI: 10.1101/614750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NCBP2modulates neurodevelopmental defects of the 3q29 deletion inDrosophilaandX. laevismodels

Abstract: 1The chromosome 3q29 deletion is associated with a range of neurodevelopmental disorders. 2 Here, we used quantitative methods to assay Drosophila melanogaster and Xenopus laevis 3 models with tissue-specific knockdown of individual homologs of genes within the 3q29 4 region. We identified developmental, cellular and neuronal phenotypes for multiple 5 homologs, potentially due to altered apoptosis and cell cycle mechanisms. We screened for 6 314 pairwise knockdowns of fly homologs of 3q29 genes, and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 128 publications
6
7
0
Order By: Relevance
“…We previously showed that many of the same fly homologs of CNV genes that showed wing defects in the current study also contributed towards neuronal phenotypes in the fly eye 41, 42 , suggesting a role for these genes in global development. We therefore performed ubiquitous and eye-specific knockdown of fly homologs to assess tissue-specific effects in comparison to the wing phenotypes.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…We previously showed that many of the same fly homologs of CNV genes that showed wing defects in the current study also contributed towards neuronal phenotypes in the fly eye 41, 42 , suggesting a role for these genes in global development. We therefore performed ubiquitous and eye-specific knockdown of fly homologs to assess tissue-specific effects in comparison to the wing phenotypes.…”
Section: Resultssupporting
confidence: 71%
“…We therefore performed ubiquitous and eye-specific knockdown of fly homologs to assess tissue-specific effects in comparison to the wing phenotypes. First, we used the da-GAL4 driver at 25°C to drive ubiquitous knockdown of RNAi lines for 31 homologs of CNV genes, including 19 that were previously published 41, 42 , and observed complete or partial lethality at larval and pupal stages with knockdown of 10/31 homologs (32.3%) ( Fig. 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently proposed model to explain phenotypic pleotropism and overlap between different microdeletions is the idea that candidate genes within each microdeleted locus interact with each other through common pathways (Jensen and Girirajan, 2019). This model has received elegant experimental support through Drosophila genetic studies (Iyer et al, 2018;Singh et al, 2019;Yusuff et al, 2019). Our findings support this idea with genetic and biochemical interactions between human and Drosophila orthologues of SLC25A1 and MRPL40.…”
Section: Discussionsupporting
confidence: 76%